Lublin i Lubelszczyzna w działalności naukowej i organizacyjnej doktora Mieczysława Buczyńskiego (2 XI 1936 - 25 XII 1992) - Czyżewski, Feliks (Slavia Occidentalis, 2019)
The article presents the academic achievements of Mieczysław Buczyński, Ph.D. (1936-1992) with special emphasis placed on his dialectological and onomastic research in the Lublin area. The scholar created a card index for the Dictionary of the Huszcza in Podlasie dialect which index consists of more than 100 thousand words. The vocabulary can serve as a basis for describing linguistic interference between the local Ukrainian dialects and the insular Polish dialect. Another area of Mieczysław Buczyński’s academic interest was onomastics, especially urban names and anthroponymy. The studies of the names in Lublin were conducted with respect to the object and the methodology. In his descriptions of urban names, Mieczysław Buczyński took into consideration the linguistic as well as the extra-linguistic factors. Anthroponyms of Armenian origin, presented with respect to the inhabitants of Zamość, played an important role in the scholar’s onomastic studies. The article presents the academic achievements of the prematurely deceased scholar and a person born and living in the Lublin area. He was involved in pioneering research and nouvelle methodology, largely supported by the ethnic and cultural diversity of the region with which Mieczysław Buczyński always identified himself.